Avicenna on heat and electricity (Texas Journal of Multidisciplinary Studies, 2022)
The article briefly reveals some of the views of the famous medieval scientist-encyclopedist Abu Ali ibn Sina (Avicenna, 980-1037) about acoustics in Physics. Based on the study of natural sciences from the physical part of the treatise "Sawdust of Nature" ("Kurozai Tabiyet"), specially dedicated to acoustics.It is characteristic that it is in this treatise that Avicenna treats some problems of acoustics from the point of view of the "science of nature" Physics" of that tim. One of them, a long one, which played an important role in the development of the theory of motion of a falling body and a body thrown at an angle to the horizon. This discussion took place between Ibn Rushd (Averroes) and Ibn Bajji (Avempas). In this discussion, the problem of the possibility and nature of the movement of the body in the void was also discussed. The article has an interdisciplinary character, written at the junction of the subject of physics and history, taking into account historical and scientific analysis.